2021
DOI: 10.1016/j.wneu.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Sustainability in a Neurosurgery Department During the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has shifted the dynamics of health care and neurosurgical practice. Elective surgeries were suspended for 8 weeks in Kentucky. Our objective was to determine if telehealth (TH) visits could be sustained as an alternative to in-person visits. Methods Deidentified data on TH usage, in-person clinic visits, and inpatient and neurosurgical case volumes from March 2, 2020 to June 26, 2020 were obtained for retrospective analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…ElGhamry et al [ 19 ] observed a 21% reduction in neurosurgical procedures in Newcastle, UK. Chau et al [ 20 ] from Kentucky, USA, indicated that their neurosurgical cases dropped 55% from their baseline. Idowu et al [ 9 ] in Lagos, Nigeria, found a 41.8% reduction in surgical procedures during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…ElGhamry et al [ 19 ] observed a 21% reduction in neurosurgical procedures in Newcastle, UK. Chau et al [ 20 ] from Kentucky, USA, indicated that their neurosurgical cases dropped 55% from their baseline. Idowu et al [ 9 ] in Lagos, Nigeria, found a 41.8% reduction in surgical procedures during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, different studies have characterized the impact of telemedicine on health care access and identified related opportunities and challenges in various medical settings [26,[33][34][35][36][37][38][39][40][41][42]. Considering the challenges of telemedicine adoption, particularly during the COVID-19 pandemic, it is crucial that future research focuses on identifying the facilitating factors and addressing the barriers to its widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has been effectively used to reduce physician exposure risks and conserve personal protection equipment (PPE) [ 3 , 11 ]. During the COVID-19 pandemic, telemedicine has been applied in different subspecialties, including neurology [ 12 ], orthopedics [ 13 ], neurosurgery [ 14 ], dermatology [ 15 ], and even in ophthalmology [ 4 ], for remote consultations and assessment. Family meetings and conversations between patients and families can be carried out by using telecommunication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%